An exploratory study of the impact of a mindfulness intervention on the well-being and self-regulation skills of children in a senior primary school setting. - Keane, Sarah (Marino Institute of Education, 2020)
Mindfulness has gained in popularity in recent years as an effective educational tool. Although gaining in popularity in Irish primary schools, it is lacking in terms of research in that context. The aim of this dissertation is to investigate the effects of a mindfulness intervention on the well-being and self-regulation skills of children in a senior primary school setting. The researcher explores the worthwhileness of using mindfulness in two senior primary school classrooms and evaluates the effects of its implementation. A qualitative approach and an interpretivist paradigm were adopted throughout this research with an element of quantitative data gathering and analysis employed. Participants included 52 sixth class students, aged between 11 and 13 years old, in a mixed, vertical school. An open-ended situation questionnaire was distributed pre-intervention, to ascertain children’s self-regulation skills. Semi-structured interviews were employed both pre- and post-intervention, with two class teachers, in order to explore teachers’ perceptions of mindfulness and its benefits within the context of the Irish primary school setting. Findings indicated that mindfulness was a beneficial addition to the classroom. Post-intervention, classroom behaviour appeared calmer and less reactive. Participants thoroughly enjoyed the mindfulness activities and they seemed to contribute to well-being and a more positive classroom climate. Mindfulness appeared to have particular effects on children with behavioural and learning difficulties, increasing their concentration skills and overall confidence.
Keywords: Research Subject Categories